Leptophilic portals to new physics at colliders - P. S. Bhupal Dev (SciPost Physics Proceedings)
Observed neutrino oscillations imply that the global lepton flavor symmetry of the Standard Model must be broken. Therefore, searches for lepton flavor violation (LFV) are promising probes of new physics beyond the Standard Model. High-energy colliders provide a powerful tool to study LFV effects, which are complementary to the low-energy charged LFV searches. Here we discuss the possibility of LFV signals at colliders arising from exotic Higgs decays, and from leptophilic scalar and vector portal scenarios.